Neuroimaging in forensic psychiatry : from the clinic to the courtroom - Simpson, Joseph R. (Wiley-Blackwell, 2012)
As neuroimaging becomes more widespread, it is increasingly being used in the courts, even though understanding and interpreting neuroimaging methods and results can be very challenging . even without attempting to evaluate their potential applications to forensic questions. The sheer volume of available information, research results, and opinions can seem intimidating to forensic practitioners and to mental health professionals in general. This will be the first book dedicated to this important topic. Designed as a reference for forensic psychiatrists, it starts with a brief overview of the psychiatric applications of the primary neuroimaging techniques currently in most widespread use, positron emission tomography (PET), single-photon emission computed tomography (SPECT), and magnetic resonance imaging (MRI). Subsequent chapters explore the current and potential uses of neuroimaging in civil and criminal forensic contexts. There is a growing body of writing on the ethical implications of neuroimaging in the legal context, but this has largely been in bioethics journals that have limited readership among members of the mental health profession. Ethical questions generated by the rapidly evolving field of forensic neuroimaging are explored in detail in a dedicated chapter. This book will be of great use to practicing forensic psychiatrists, forensic psychologists and forensic neurologists as they are increasingly likely to find themselves being asked to give professional opinions regarding the impact of neuroimaging findings on medicolegal questions such as competence, criminal responsibility, personal injury and disability.